Dampak Penerapan Educative Song Dalam Pembelajaran Bahasa Inggis Pada Anak Usia Dini - Faiza Hawa; Rahmawati Sukmaningrum; Arso Setyaji (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2023)
As as international language used across the globe, English needs to be given to students since their early age. For that reason, government issued a policy concerning the implementation of English learning to be given to students since early age. Teachers in class are facing a challenging situation since they have to be able to create fun, creative English larning which involve early age students in its implementation. What should they do then to realize such fun and attractive Engllish learning? An attractive and educative learining media can help teacher to make it realized. Educative song is an educative media that can make learning English fun and attractive. What effects these educative songs can bring in English learning? This is the focus of this study. This study aimed at finding out the effect of implementing educative song as a media for learning English for pre-school students. This study is designed as a descriptive qualitative study which involves pre-school teachers. In order to get the data, the researchers employed a 5 Likert-scale questionnaire to 40 pre-school teachers across Guntur subdistrict, Demak Regency, in Central Java Province. The data were then analyzed using Interactive Model Analysis by Miles and Huberman. The results displayed some important notes. Learning English through educative songs can build students’ good character, attitude, and confidence. Furthermore, educative songs motivated students to learn more for English. The songs also help students to enrich their English vocabulary. For this, pre-school teachers should provide students with fun learning in learning English in school.